Frontispiece: Boosting the Energy Density of Carbon‐Based Aqueous Supercapacitors by Optimizing the Surface Charge. Issue 20 (8th May 2017) - Yu, Minghao; Lin, Dun; Feng, Haobin; Zeng, Yinxiang; Tong, Yexiang; Lu, Xihong
Abstract : Aqueous Supercapacitors In their Communication onpage 5454 ff., X. H. Lu et al. report a precharging strategy to tune the surface charge of porous carbon electrodes. The operating voltage of carbon‐based aqueous supercapacitors was significantly expanded.